Peridynamic analysis of drill-induced borehole damage. (October 2019) - Chen, Jingkai; Jiang, Wenchun; Wang, Qi; Zhang, Yanting
Abstract: The borehole stability is crucial in well-drilling and oil-production operations. Before drilling, the rock at certain depth is in equilibrium state with its surrounding formation. This balance is disturbed when the borehole is created by the drill bit. Although the borehole-related problems are influenced by complex factors, including weak formation properties, tectonic stress state, fluid-related problems and etc., understanding the drill-induced borehole damage is critical before further investigating the borehole instability. In this paper, the damage of the borehole induced by the drill bit is analyzed based on the state-based peridynamics. The damage of the formation is expressed in the form of 'broken bonds'. The bond break criterion, local damage criterion and bit penetration criterion are proposed for the drilling modeling. The heterogeneous properties of the formation rock are modeled stochastically by modifying peridynamic constitutive parameters. The natural discontinuities of rock are represented by the artificially breaking bonds in the initially-cracked region. The geometries of discontinuity, including spacing, orientation, persistence and etc., are modeled by following the particular statistical distributions. Thus, the crack propagation of formation rock under the drilling operation is captured. In this peridynamic model, the borehole damage propagations under the influence of discontinuity surfaces and multi-layer interfaces are analyzed. This research investigates the drill-induced borehole damage, which casts light on the guideline for the borehole instability control and the drilling operations. Highlights: The properties of formation, including rock heterogeneities, formation discontinuities and multiple formation layers, are represented within peridynamic framework. Peridynamic formation damage criteria, including bond break criterion, local damage criterion and bit penetration criterion, are reformulated. A numerical adaptive peridynamic model is proposed to simulate the process of drill bit penetration and formation damage propagation. Drill-induced borehole damage characteristics are analyzed by considering the heterogeneities, discontinuities and multi-layers of the formations. The coupling of discontinuous joints with the nonlocal parameter is discussed.